Human Resource Information System: Bridge of Strategic Human Resource Practices and HR Department Performance of Manufactures in Klang Valley, Malaysia - Lum, Tze Choong (2012)
This research is to examine the relationship between the usage of Human Resource Information System (HRIS), Strategic Human Resource Management (SHRM) practices and Human Resource (HR) department performance. Utilizing the quantitative method, questionnaires was distributed to 300 of manufactures within Klang Valley, Malaysia. A total of 80 valid responses were obtained and the results showed that the usage of HRIS is positively related to the SHRM practices. However, there is no significant relationship between SHRM practices and HR department performance. This study proves that SHRM practices can be improved by the usage of HRIS and the study may contribute to the industry in the decision making process of investing in HRIS within the organization.